Body satisfaction, problematic smartphone use, sleep deprivation, and psychological well-being in adolescents: A half-longitudinal serial mediation study - Yildirim-Kurtulus, Hacer; Deniz, Mehmet Engin; Satici, Seydi Ahmet (SAGE PUBLICATIONS LTD, 2025)
The relationships between body satisfaction, problematic smartphone use, sleep deprivation and psychological well-being have been examined with cross-sectional methods. However, the lack of any longitudinal study in which these variables were examined together made it necessary to conduct this study. In this study, we tested whether problematic smartphone use and sleep deprivation serially mediate the relationship between body satisfaction and psychological well-being. After matching the data obtained from the first (T1) and second waves (T2) of the study, the final sample consisted of 222 Turkish adolescents (M = 14.08 years, SD = 0.70). For this purpose, a study was conducted in two separate time waves and structural equation modeling was used to test longitudinal serial mediation between variables. According to the results, problematic smartphone use and sleep deprivation play a serial mediating role in the longitudinal relationship between body satisfaction and psychological well-being.
Keywords: body satisfaction; longitudinal; problematic smartphone use; psychological well-being; sleep deprivation; DEPRESSIVE SYMPTOMS; INTERNET-USE; IMAGE SATISFACTION; YOUNG-ADULTS; SELF-ESTEEM; DISSATISFACTION; ADDICTION; WEIGHT; HEALTH; BOYS; Psychology